2020
DOI: 10.28945/4491
|View full text |Cite
|
Sign up to set email alerts
|

E- Assessment with Multiple-Choice Questions: A 5 Year Study of Students’ Opinions and Experience

Abstract: Aim/Purpose: The aim of this study is to understand student’s opinions and perceptions about e-assessment when the assessment process was changed from the traditional computer assisted method to a multiple-choice Moodle based method. Background: In order to implement continuous assessment to a large number of students, several shifts are necessary, which implies as many different tests as the number of shifts required. Consequently, it is difficult to ensure homogeneity through the different tests and a huge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Nevertheless, most papers focused on summative assessment based on Moodle quizzes investigating both teachers’ and students’ opinions when implementing multiple-choice questions (Babo & Suhonen, 2018 ; Cakiroglu et al, 2017 ; Dimic et al, 2018 ; McKenzie & Roodenburg, 2017 ; Shdaifat & Obeidallah, 2019 ). According to a 5-year study, the ‘luck’ factor associated with multiple-choice questions is fair (Babo et al, 2020 ). Studies that have investigated the students' point of view indicate that the students agree that Moodle is easy to use and complements teaching, although most students still prefer classical assessment techniques (Cakiroglu et al, 2017 ; McVey, 2016 ; Popovic et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, most papers focused on summative assessment based on Moodle quizzes investigating both teachers’ and students’ opinions when implementing multiple-choice questions (Babo & Suhonen, 2018 ; Cakiroglu et al, 2017 ; Dimic et al, 2018 ; McKenzie & Roodenburg, 2017 ; Shdaifat & Obeidallah, 2019 ). According to a 5-year study, the ‘luck’ factor associated with multiple-choice questions is fair (Babo et al, 2020 ). Studies that have investigated the students' point of view indicate that the students agree that Moodle is easy to use and complements teaching, although most students still prefer classical assessment techniques (Cakiroglu et al, 2017 ; McVey, 2016 ; Popovic et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, this study suggests that both faculty members and students should be helped with training sessions to get familiar with the online assessment techniques. Furthermore, online assessments should be harmonized with other techniques to accomplish the projected learning objectives (Babo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the design of formative online assessment through quizzes, the key publications suggest that quizzes should not only include true or false questions but a mixture of types (López-Tocón, 2021). Other studies found that quizzes are a well-suited form of online assessment for theoretical knowledge, but not necessarily for practical knowledge and should therefore be combined with other forms of online assessment, such as project-based learning or further homework tasks (Babo et al, 2020). While a higher correlation between final exam performance and the performance on formative quizzes with limited time and attempts was found (MacKenzie, 2019), unlimited attempts in general lead to a higher performance in the final exam (Davis et al, 2020).…”
Section: Summary Of Results For Rq2mentioning
confidence: 99%
“…Implementation type: Automated assessment was mostly used on quizzes. Quizzes included all sorts of tasks that did not require students to write longer answer, such as multiplechoice questions, single-choice questions, blank-filling or crossword-type tests (Admiraal et al, 2015;Azevedo et al, 2022;Babo et al, 2020;Bacca-Acosta & Avila-Garzon, 2021;Bekmanova et al, 2021;Carpenter et al, 2017;Chaudy & Connolly, 2018;Davis et al, 2020;Dermo & Boyne, 2014;Förster et al, 2018;Gamage et al, 2019;Gámiz Sánchez et al, 2014: Guerrero-Roldán & Noguera, 2018Hughes et al, 2020;Huisman et al, 2018;Kühbeck et al, 2019;López-Tocón, 2021;Mao & Peck, 2013;Meek et al, 2017;Mora et al, 2012;Ortega-Arranz et al, 2019;Reilly et al, 2016;Ross et al, 2018;Sancho-Vinuesa et al, 2018;Schaffer et al, 2017;Shaw et al, 2019;Stratling, 2017: Taghizadeh et al, 2014Tempelaar, 2020;Thille et al, 2014;Wilkinson et al, 2020). Automated assessment, including Natural Language Processing, was also used on short-answer questions (Carnegie, 2015;Chen et al, 2018;Ellis & Barber, 2016), or tasks including longer texts (Reilly et al, 2016;Santamaría Lancho et al, 2018;Xian, 2020).…”
Section: Assessment Mode: Automated Assessmentmentioning
confidence: 99%
See 1 more Smart Citation